Development of energy recuperation system for the dc third rail system - Siti Farhana, Faridudin (2022)
In line with the initiative in achieving zero carbon emission in 2050, railway industries are developing a railway system with electric train rolling stock. These electric trains are equipped with the capability of regenerative braking which reduce the usage of mechanical braking onboard. Various methods and techniques are introduced on the recuperative regenerative train braking such as resistor units, inverters and energy storage systems. I n this research, we will observe the characteristic of nonregenerative and regenerative electric train with the effects on current, voltage, power and energy addition, we will evaluate to the traction system the amount of energy produced from regenera. Intive braking to determine a better solution of energy recuperative system either battery energy storage system or an inverter system to enhanced the resistive unit system implemented previously. With the current increase of electricity tariff year by years, the asset owner and operators are suffering with the high amount of energy billing to operate the railway system. Hence, traction system that equipped with resistor units may consider to upgrade the system in incorporating an inverter system or an energy storage system which will reduce the peak demand power consumption and obtain the benefits of re recovered energy.